Project Management Maturity: A Case Study of Payne in Nottingham - Kotogianni, E (2011)
Project management is broadly used in companies and it is considered as a significant tool in a broadly altering business environment. This dissertation is a case study of Payne Company in Nottingham and describes the project management maturity “phenomenon” in organisations. The objective of this dissertation is to assess the maturity level of Payne, a project-based company, identify “possible” weaknesses and recommend improvements. The term “maturity” means in simple words “how well a company manages its projects”. As part of the goal, some of the most used maturity models have been outlined and Portfolio, Programme and project Management Maturity model (P3M3) has been selected for estimating the maturity level of Payne Company in terms of project management (PM). The purpose is for benefits of applying a maturity model to be identified and for an optimal maturity level of Payne to be suggested. This case study provides a way of checking how the theory of Project management is implemented in practice.